2023
DOI: 10.3390/en16020810
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Fish Motion through a Diagonal Reversible Turbine

Abstract: Utilization of unharnessed hydro-power necessitates designing fish-friendly hydraulic machinery. Towards this effort, the present work investigates various methods for tracking fish motion, ranging from particle tracking methods to accurate, but computationally expensive, body tracking methods, such as immersed boundaries and overset meshes. Moreover, a novel uncoupled 6-Degree of Freedom tracking technique is proposed, based on an approximated pressure field around the tracked body of interest, using steady-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The major underlying assumption is that the body mass of the tracked object is insignificant compared to the flow momentum; hence, it does not significantly alter the flow field. Numerical experiments have shown that this assumption seems valid when considering fish sizes with characteristic dimensions at most 50 times smaller than a turbine (see [105,108]); indeed, the predicted trajectory with the uncoupled fast tracking is very similar to the fully coupled 6-DoF either with immersed boundaries [105] or overset meshes [108], in the case of axial and diagonal (Deriaz)-type turbines. A recent variant [108] to the more computationally expensive 6-DoF techniques decouples the flow field from the body tracking.…”
Section: Fully Coupled 6-degrees-of-freedom (6-dof); Overset Meshesmentioning
confidence: 87%
See 4 more Smart Citations
“…The major underlying assumption is that the body mass of the tracked object is insignificant compared to the flow momentum; hence, it does not significantly alter the flow field. Numerical experiments have shown that this assumption seems valid when considering fish sizes with characteristic dimensions at most 50 times smaller than a turbine (see [105,108]); indeed, the predicted trajectory with the uncoupled fast tracking is very similar to the fully coupled 6-DoF either with immersed boundaries [105] or overset meshes [108], in the case of axial and diagonal (Deriaz)-type turbines. A recent variant [108] to the more computationally expensive 6-DoF techniques decouples the flow field from the body tracking.…”
Section: Fully Coupled 6-degrees-of-freedom (6-dof); Overset Meshesmentioning
confidence: 87%
“…Numerical experiments have shown that this assumption seems valid when considering fish sizes with characteristic dimensions at most 50 times smaller than a turbine (see [105,108]); indeed, the predicted trajectory with the uncoupled fast tracking is very similar to the fully coupled 6-DoF either with immersed boundaries [105] or overset meshes [108], in the case of axial and diagonal (Deriaz)-type turbines. A recent variant [108] to the more computationally expensive 6-DoF techniques decouples the flow field from the body tracking. This decoupling makes it possible to solve the flow field with steady-state moving reference frames, which greatly speeds up the solution by roughly two orders of magnitude, allowing for the derivation of statistics (see indicatively Figure 10, where a specifically designed reversible, fish-friendly Deriaz turbine [109] was tested).…”
Section: Fully Coupled 6-degrees-of-freedom (6-dof); Overset Meshesmentioning
confidence: 87%
See 3 more Smart Citations